$\begin{array}{1 1}2 \sqrt{10} \\ 2 \sqrt {26} \\ 0 \\ 4 \sqrt{5} \end{array} $

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

- Distance between two points $(x_1,y_1,z_1)\:\;and \:\:(x_2,y_2,z_2)$ is given by $\sqrt {(x_2-x_1)^2+(y_2-y_1)^2+(z_2-z_1)^2}$

Given two points are $A(-1,3,-4)$ and $B(1,-3,4)$.

We know that the distance between two points $(x_1,y_1,z_1)\:\;and \:\:(x_2,y_2,z_2)$ is given by $\sqrt {(x_2-x_1)^2+(y_2-y_1)^2+(z_2-z_1)^2}$

Here $x_1=-1,\:y_1=3,\:z_1=-4$ and

$x_2=1,\:y_2=-3,\:z_2=4.$

$\therefore$ The distance between the give two points $AB$ is

$\sqrt {(1+1)^2+(-3-3)^2+(4+4)^2}=\sqrt {4+36+64}=\sqrt {104}=2\sqrt {26}$

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...